Implementation of postgenomic technologies for cancer research. Institutional experience - RUDGALVYTĖ, Martina; STANČIŪTĖ, Diana; BIELSKIENĖ, Kristina; JONUŠIENĖ, Violeta; KIRVELIENĖ, Vida; SUŽIEDĖLIS, Kęstutis; ATKOČIUS, Vydmantas; VALUCKAS, Konstantinas Povilas (Acta medica Lituanica, 2010)
Advance in molecular biology and the new technologies for biomedical research are being rapidly introduced into the research of complex pathologies worldwide. Implementation of these technologies, however, needs substantial financial resources for the equipment and for training the specialists. The rapid development of biomedical research over the past decade increases the risk of moral ageing of the implemented technologies and raises doubts as to whether countries with limited financial resources could afford them. In this article, we share our institutional experience in the implementation of post-genomic technologies in cancer research in Lithuania and stress the need of modern infrastructure in biomedical research, despite the needed efforts and associated risks.Keywords: postgenomic technologies, cancer research